Schedule Acceleration Planning in Construction Project (Case Study: Japek II Selatan Tollroad) - Aziz Irsyad; Ika Arum Puspita; Wawan Tripiawan (School of Industrial and System Engineering, Telkom University, 2022)
This study focuses on the remaining work at stations (STA) 53+950 to 54+550 in Jakarta – CikampekII Selatan Toll Road Package III project to find the critical path, completion durations, and projectcosts before and after acceleration. The CPM Technique was used to compile network planningdiagrams, determine the critical path and project duration. Crashing Project was applied to crashschedule through the total project duration and cost whose changes due to the implementation of thecrashing method. The critical path was found in mobilization, tree felling, clearing, dig and haul,borrow material, subgrade preparation, base course (A grade), subbase course (B grade), drainagelayer, lean concrete (t=10 cm), concrete pavement, concrete barrier type B, and signage. In the CPM,the duration of project completion is 214 days. The total project budget under normal circumstancesis Rp22.073.412.654. After accelerating with the Crashing Project by proposed overtime was obtainedthe reduced total cost of Rp32.004.882 from the total normal cost of Rp22.073.412.654 toRp22.041.407.771 with an optimum duration of 183 days